The Influence of Electronic Word of Mouth and Product Diversity on Purchasing Decisions for Hanasui Cosmetic Products - Nur'aini, Zulfa Afifah; Utami, Datien Eriska (Al Tijarah, 2024)
This study analyzes the influence of Electronic Word of Mouth (E-WOM) and product diversity on purchasing decisions for Hanasui cosmetics in Klaten. The primary objective of this study is to understand how these two factors influence consumer behavior in determining product choices.The study employed a quantitative survey method, distributing questionnaires to 100 respondents. IBM SPSS Statistics v23 x64 was used to analyze the data to obtain accurate and valid results. The findings of the study indicate that both E-WOM and product diversity exert a significant positive influence on purchase decisions, thereby confirming that effective marketing strategies, including the utilization of digital consumer reviews and the provision of a wide product variety, play an important role in increasing consumer attraction and interest in Hanasui cosmetic products.